Monetary Policy Implementation : Results from a Survey - Buzeneca, Inese; Maino, Rodolfo (Washington, D.C. : International Monetary Fund, 2007)
Since the early 1990s, the IMF has been advising countries to shift to the use of indirect instruments for executing monetary policy. This paper provides information about a monetary policy instruments database, maintained by the Monetary and Capital Markets Department of the IMF. We offer an overview of the information contained in the database in the form of comparative summary tables and graphs to illustrate the use of monetary policy instruments by groups of countries (developing, emerging market and developed countries). The main trend that can be identified from the database information is the increasing reliance on money market operations for monetary policy implementation. We emphasize the relevance and usefulness of the data collected through periodic surveys of central banks, for general descriptive and analytical purposes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet